(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
منذ اكتشاف جرثومة الملتوية البوابية ومسؤوليتها عن العديد من الأمراض وخاصة تلك المتعلقة بالمعدة بدءاً من عسر الهضم... التهاب المعدة... القرحة وانتهاء بالأورام الخبيثة المعدية والبحث عن معالجة فعالة للتخلص من هذه الجرثومة بغية الشفاء من المرض والحد من انتشاره متواصل. ويستمر عدد الأدوية المستخدمة والبروتوكولات الدوائية المتبعة في تزايد مستمر. إن الهدف من هذه الدراسة هو تحديد بدقه البرتوكول الأنجح في الشفاء من هذه الجرثومه باستخدام عقار مثبط لمضخة البروتون مع نوعين من الصادات الحيوية حيث عولج 257 مريضاًًًً ثبت لديهم الإصابة والأنتان المعدي بالملتوية البوابية توزعوا على الشكل التالي 138 ذكراً و119 أنثى تراوحت أعمارهم بين 17 – 72 سنه وقسموا إلى أربع مجموعات تلقوا أربع مجموعات دوائية مختلفة أظهرت فعالية متفاوته في العلاج حيث كان أفضلها المجموعة التي حوت مركب Tinidazol سواء مع مركب كلاريترومايسين أو أموكسسسيلين ويمكن اعتباره العقار المفضل. Since the discovery of Hilecobacter pylori and its responsibility for multi diseases especially those which are related to stomach, for example: dyspepsia ,gastritis, ulcer and malignant gastric tumers, and the research for effective treatment for getting rid of this organ in order to recover from diseases and prevent its spreading, The researches continue and the number of drugs used and the medical protocols have been increasing. The aim of this study is the exact detection of the best protocol for iriadicatian of Hileco bacter pylori by using a drug. Includiug inhibitor of proton’s pump, and two types of anti biotics. 257 patients who had an infection of stomach with hilecobacter pylori were divided as the following: 138 male, 119 female and their ages ranged between 17-72 years. The patients were divided into four groups, they were treated by four different medical protocols wich were affective in the treatment. The best protocols, which contains Tinidazol with claritromycin or Amoxycillin, so we can consider it as drug of choice.